IMPLEMENTATION OF GUIDED INQUIRY-BASED LEARNING MODEL TO IMPROVE STUDENTS’ CREATIVITY THINKING SKILL - Oktavia, Rela Setyawati (Universitas Negeri Surabaya, 2019)
The study aims to implement learning media guided inquiry-based to improve students’ creativity thinking skill of grade X on Pteridophyte material. The type of research was pre-experimental study which used one class without a control class. The study was conducted on March 2019. The research subject was 22 senior high school students of grade X on Pteridophyte sub material. The research design was One Group Pretest-Posttest Design. The learning media used was lesson plans, student activity sheets, and creative thinking test instruments. The research instrument used was the observation sheet of learning model implementation, the activities of students and the instruments test of creative thinking skills. The data result of creative thinking skills’ pre-test and post-test was analyzed by N-Gain analysis which was the result of the students’ progress of creative thinking skill after learning conducted. The conclusion was the implementation of guided inquiry-based learning model on Pteridophyte material to improve students’ creativity thinking skill. This can be seen from the results of students' thinking skills tests that improved after posttests. Keywords: guided inquiry-based learning, Pteridophyta, creative thinking skills.